Mind the grass! Exploring the assessment of informant coverage in policing and law enforcement. Issue 1 (2nd January 2019) - Atkinson, Colin
ABSTRACT: The use of informants, or Covert Human Intelligence Sources (CHIS), has become a mainstay of contemporary policing and law enforcement in the United Kingdom as police, security and enforcement agencies seek to tackle a range of crimes. Recognising the relative paucity of enquiry on this subject, and addressing the associated requirement for further empirical research, this paper explores how 'informant coverage' – the extent to which informants can provide information on targets, suspects, crimes, and criminal conspiracies – is assessed in policing and law enforcement in Scotland. It is principally informed by qualitative research conducted in 2017 and 2018, comprised of semi-structured interviews with 19 participants. Drawing upon a thematic analysis of the resultant data, and enriched by the author's prior experience as a practitioner in this field, this paper identifies the strengths and limitations of established practices. Additionally, this paper highlights the emerging role of analysis, and the contribution of the intelligence analyst, in this specialist area of intelligence work. It concludes that if analysis is to make a valuable and continuing contribution to the effective use of informants in future practice then sustained proactive leadership will be required to support such innovative approaches.